Single molecule secondary structure determination of proteins through infrared absorption nanospectroscopy - Francesco Simone Ruggeri (Nature Portfolio, 2020)
While infrared nanospectroscopy methods based on thermomechanical detection (AFM-IR) enables the acquisition of absorption spectra at the nanoscale, single molecule detection has not been possible so far. Here, the authors present off-resonance, low power and short pulse infrared nanospectroscopy (ORS-nanoIR), which allows measuring infrared absorption spectra at the single molecule level in a time scale of seconds with high throughput and demonstrate that the secondary structure of single protein molecules can be determined with this method.